Building Long-Term Portfolio Benchmarks for Pension Funds in Emerging Economies - Rudolph, Heinz P.; Sabat, Jorge (World Bank, Washington, DC, 2016)
The movement from a defined benefit to a defined contribution pension system has important implications in the area of portfolio allocation. While the focus of defined benefit pension funds is essentially in the long term, some defined contribution funds might have incentives to invest with shorter-term horizons. The case of open pension funds, such as the ones in several countries in Latin America and Central and Eastern European countries, shows that competition on short-term returns may bring pension funds into suboptimal portfolio strategies. As policy makers become increasingly interested in finding long-term sources of financing for infrastructure and other long-term projects, it becomes essential to upgrade the regulatory framework of open pension funds. This paper contributes to the literature by proposing an investment regulatory framework based on strategic asset allocation that can be applicable to open pension funds. Based on the use of lifecycle investment strategies, the paper proposes the implementation of common portfolio benchmarks for pension funds. Three elements are emphasized for implementation of strategic asset allocation: (a) a well-defined pension objective, (b) sound governance of the portfolio benchmark, and (c) a methodology for developing the benchmark. The paper proposes the use of the approximation methodology as a starting point for designing portfolio benchmarks, and illustrates step-by-step how to build these long-term portfolios in a didactical way.